Aktywność ekonomiczna przedsiębiorstw małej i średniej skali w Polsce - Paulina Filip (Przedsiębiorczość - Edukacja, 2010)
SME sector in the polish market economy and in another countries are growing rapidly last times.Small and medium-sized enterprises are a valuable resource for countries with developedmarket economy. They have importance role in the Polish economy and a great influence fortheir development. The development of this sector is related to the numerous circumstanceslike the development of national economy, economy structure and conditions, financial stateand local governments as well economic policies. The researches in this area should know allthe circumstances, to eliminate their negative impact and get propositions to economic policy,which allows eliminating these barriers.The analysis of small and medium businesses, which will be presented in the article wascarried out for the period 1994–2007.The analyses were based of statistical data obtained fromCSO. Based on these data have been done analysis of small and medium businesses. In thearticle has shown the level of investment expenditures, economic and financial results MSP’sector in last years received positive indicator as the results of own activity.